Calcifications and tungsten deposits after breast-conserving surgery and intraoperative radiotherapy for breast cancer. Issue 12 (December 2015) - Jalaguier-Coudray, Aurélie; Cohen, M.; Thomassin-Piana, J.; Houvenaeghel, G.; Villard-Mahjoub, R.; Tallet, A.; Minsat, M.; Resbeut, M.
Highlights: To our knowledge, this is the first report of calcifications associated with proven tungsten deposits. These deposits were due to the use of shielding devices, which are largely composed of tungsten. Because of this potential complication and their questionable utility, shielding devices are no longer used at our institution. Abstract: Aim: To describe the presence of atypical calcifications on post-operative mammography after breast-conserving surgery (BCS) and intraoperative radiotherapy (IORT). Materials and methods: We retrospectively include all patients followed after BCS and IORT for breast cancer ( n  = 271). All follow-up mammograms at 6 months after surgery were retrospectively evaluated by two board-certified radiologists. The radiologists had to notify the presence or the absence of atypical calcifications. Results: Five patients had on follow-up mammography the presence of atypical calcifications. Two patients had a stereotactic breast biopsy. The pathologic examination showed the presence of small tungsten particles located in the breast parenchyma. Conclusion: The presence of atypical calcifications after BCS and IORT, presenting as multiple, scattered, round calcifications, should be rated as BIRADS 2 and do not require biopsy. They corresponded on tungsten deposits.